Intragenomic conflict associated with extreme phenotypic plasticity in queen-worker caste determination in honey bees (Apis mellifera) - Sean T. Bresnahan; Shaun Mahony; Kate Anton; Brock Harpur; Christina M. Grozinger (Genome Biology)
Abstract Background Caste determination of honey bees (Apis mellifera) exemplifies developmental plasticity, where differences in larval diet result in identical genotypes yielding either long-lived, reproductive queens or short-lived, facultatively sterile workers. Beyond environmental factors, intragenomic conflict between genes inherited from the mother (matrigenes) versus the father (patrigenes) is hypothesized to influence the underlying traits. In honey bees, the Kinship Theory of Intragenomic Conflict predicts selection on patrigenes to favor traits enhancing individual fitness, such as accelerated growth or increased body size—traits more active in queen-destined larvae. Although parent-of-origin effects have been reported in honey bees, the associated gene regulatory mechanisms remain unknown. While DNA methylation underlies parent-biased transcription in eutherians, angiosperms, and some insects, it is not operating in honey bees or other social insects. Results Allele-specific transcriptome analyses on queen- and worker-destined larvae at 192 h post-fertilization (hpf) reveal hundreds of genes with parent-of-origin effects, with queen-destined larvae showing overrepresentation of patrigene-biased transcription relative to worker-destined larvae. Genes with parent-biased transcription resemble imprinted genes in other taxa regarding genomic clustering, recombination rate, intron length, and CpG density, with a subset showing parent-biased transcription in 24 hpf eggs. Allele-specific ChIP-seq analyses demonstrate that parent-of-origin effects on caste-specific profiles of H3K27me3, H3K4me3, and H3K27ac are associated with parent-of-origin transcription. Conclusions These findings suggest that parent-of-origin intragenomic conflict may influence phenotypic plasticity and may be associated with histone post-translational modifications, suggesting a “noncanonical” genomic imprinting-like system in social insects.